2003
DOI: 10.1192/bjp.182.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Flashbacks and post-traumatic stress disorder: the genesis of a 20th-century diagnosis

Abstract: Although this study raises questions about changing interpretations of post-traumatic illness, it supports the hypothesis that some of the characteristics of PTSD are culture-bound. Earlier conflicts showed a greater emphasis on somatic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 20 publications
(17 reference statements)
2
73
1
2
Order By: Relevance
“…Historians have recently adduced evidence seemingly inconsistent with Brewin's theory about a special mechanism subserving flashbacks (Jones et al, 2003). Scrutinizing British medical military archives, they found that psychiatrically traumatized soldiers in World War I and World War II almost never reported anything akin to the flashback experiences mentioned by trauma survivors much later in the twentieth century.…”
Section: Problems With the Symptomatic Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Historians have recently adduced evidence seemingly inconsistent with Brewin's theory about a special mechanism subserving flashbacks (Jones et al, 2003). Scrutinizing British medical military archives, they found that psychiatrically traumatized soldiers in World War I and World War II almost never reported anything akin to the flashback experiences mentioned by trauma survivors much later in the twentieth century.…”
Section: Problems With the Symptomatic Criteriamentioning
confidence: 99%
“…Kardiner's cases raise the possibility that the scrutinizing of British military archives by Jones et al (2003) only demonstrated that British doctors simply failed to ask the right questions of their patients, thus leading to the near-absence of flashbacks from the military medical records (Jones et al, 2003; see also Kimbrell, Myers, & Freeman, 2003).…”
Section: Problems With the Symptomatic Criteriamentioning
confidence: 99%
“…It is curious to note that few patients describe their perceptions as exact representations of sensations experienced at the time of the trauma (Van Der Kolk, 1997;2006). The permeability of traumatic memories, to cultural influences and changes of their expression over time has been demonstrated (Jones et al, 2003). Van der Kolk (1997) investigated the differences in recovering memories of traumatic experiences from recovering memories of significant but non-traumatic events.…”
Section: Trauma and Memory Systemsmentioning
confidence: 99%
“…The term psychic trauma was firstly coined by Freud (1895) during his studies on the aetiology of neurosis, in which he stated that psychic traumatism is characterized by excessive excitement related to an individual's tolerance and capacity to integrate and psychically elaborate this stimulus. However, characterization of an event as traumatic does not depend only on the stressor stimulus, and there is no single human response to the same traumatic events or a "universal reaction to trauma" (Jones et al, 2003). The search to understand idiosyncratic responses to trauma has turned to the contribution of personality factors (Bonanno et al, 2004), with the way people process the stressor event appearing to be a critical factor in determining whether an event will be encoded as traumatic or not .…”
Section: Trauma and Memory Systemsmentioning
confidence: 99%
“…2,3 Some studies revealed that there is a degree of interindividual variability in the processing of memory of life events and basic emotions, 4 which deviates the focus from the idea of "universal reaction to trauma." 5,6 Many victims of trauma look for professional aid, literature, supervision, and friendship, while others focus on the collapse and/or victimization. 7 Even though there are some significant qualitative differences in how traumatized and non-traumatized people process and categorize their own experiences, 8 …”
Section: Introductionmentioning
confidence: 99%